2015
DOI: 10.1007/5584_2015_154
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease in Children with Cystic Fibrosis

Abstract: Previously published studies have indicated that gastroesophageal reflux (GER) disease is common in pediatric patients with cystic fibrosis. The aim of the present study was to get insight into the incidence of GER and to characterize the nature of reflux episodes in children with cystic fibrosis. This was a multicenter, prospective study of children with cystic fibrosis older than 18 months. Forty four consecutive patients (22 boys, mean age 10.4 ± 3.6, range 3.0-17.8 years) were enrolled into the study. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
(32 reference statements)
0
25
0
1
Order By: Relevance
“…Gastroesophageal Reflux Disease (GERD) has a complex pathogenesis, and its intensification may directly impact the progression of bronchopulmonary dysplasia. 9 Increased pain and flatulence may be caused by Distal Intestinal Obstruction Syndrome (DIOS). Partial DIOS is diagnosed when the fecal mass is retained in the ileocecal area.…”
Section: Introductionmentioning
confidence: 99%
“…Gastroesophageal Reflux Disease (GERD) has a complex pathogenesis, and its intensification may directly impact the progression of bronchopulmonary dysplasia. 9 Increased pain and flatulence may be caused by Distal Intestinal Obstruction Syndrome (DIOS). Partial DIOS is diagnosed when the fecal mass is retained in the ileocecal area.…”
Section: Introductionmentioning
confidence: 99%
“…The authors could not find a relation between gastric emptying and MIIpH results in children with cystic fibrosis (CF) [15]. Acidity of the refluxate may also relate to a localized proximal gastric area called 'the gastric acid pocket' that may persist even in the postprandial period when (the rest of the) stomach content is neutralized by the meal [16].…”
Section: Pathophysiologymentioning
confidence: 98%
“…Seven of the 10 articles were eligible for detailed analysis of GERD incidence in pediatric CF cohorts (►Table 1). [11][12][13][14][15][16][17] In total, there were 212 children with CF available for analysis, of which 108 (51%) were male. The median number of patients in the study cohort was 28 (range, 8-44) with an age range from 0.5 months to 20 years.…”
Section: Overall Incidence Of Gerdmentioning
confidence: 99%
“…[12][13][14][15] Two later articles (published in 2015 and 2016) used pH-impedance monitoring to investigate GERD and the diagnosis were based on RIs >6 and >5%, respectively. 16,17 However, symptom correlation for pH or pH-impedance studies was not included in their methodologies. Dziekiewicz et al specifically reported that they were unable to calculate symptom correlation parameters as patients or their parents did not note any specific symptoms.…”
Section: Gerd Diagnosis and Incidence In Cf Childrenmentioning
confidence: 99%